Dominion Road: the shifting urbanscape - Ho, KT (Photowhisper, 2011)
The Dominion Road project is a photographic project proposed and developed by King Tong HO, the Chairman of Photowhisper Incorporated. Its intention is to explore the ongoing cultural activities on Dominion Road and, in time, to develop a photo-based archive to represent the creative works of New Zealand Chinese photographers, and to support the historical and cultural studies of the local communities.